Port Site and Intraperitoneal Infiltration of Local Anesthetics in Reduction of Postoperative Pain after Laparoscopic Cholecystectomy - Alam, Mohammad Shaha; Hoque, Hasnat Waheedul; Saifullah, Mohammad; Ali, Md Omar (Medicine Today, 2010)
Laparoscopic cholecystectomy is now the gold standard technique for the treatment of gallstones disease. Although pain after laparoscopic cholecystectomy is less intense than after open cholecystectomy, some patients still experience considerable discomfort during the first 24 to 72 postoperative hours. The aim of this study is to evaluate the effect of intraperitoneal and port site instillation of local anaesthetics on pain relief in early postoperative period following laparoscopic cholecystectomy. Fifty patients undergoing elective laparoscopic cholecystectomy were consecutively included in this study and sample was divided into two groups. Following removal of gallbladder, Group A received 20 ml of 0.25% bupivacaine instilled in the right sub diaphragmatic space and 20 ml of 0.25% bupivacaine in divided doses at the trocar sites. The evaluation of postoperative pain was done at fixed time interval according to the numerical verbal scale and the dosage of narcotic analgesics consumed was also recorded. Mean pain scores at 6 hours and at 12 hours after surgery were 6.02 and 4.72 respectively, in the bupivacaine group compared with 8.44 and 6.08 respectively in the control group (p= <0.001 and <0.001). However, pain scores at 24 hours and 48 hours postoperatively and incidence of shoulder tip pain did not differ significantly between the two groups. The mean total narcotic analgesics used in study group was 1.91 as compared to 2.50 in the control group respectively and was found to be statistically significant (p= <0.001). Infiltration of bupivacaine in to port site and intraperitoneal space is simple, inexpensive and effective technique to minimize early postoperative pain and can be practiced for elective laparoscopic cholecystectomy. DOI: 10.3329/medtoday.v22i1.5601 Medicine Today Vol.22(1) 2010. 24-28